Integrating Pedagogical Translanguaging and Multimodality in EFL Classroom: A Secondary School Case - Apriyanti, Nurlita; Samsi, Yogi Setia; Wachyudi, Kelik (Papanda Publisher, 2026)
This study aims to explore the types of translanguaging and strategies used by EFL teachers integrated with multimodal approaches in the learning process, as well as students' experiences with these translanguaging practices in the classroom. This study uses a qualitative approach with a case study design. Data were collected through classroom observation and semi-structured interviews to analyze translanguaging practices and multimodal use, using observation sheets and interview guides as instruments. The data were then analyzed using Thematic Analysis to identify patterns of translanguaging and student experiences. The results showed that teachers predominantly used Intersentential Translanguaging (50%) and Managerial Strategy (51.2%) in explaining concepts and managing the classroom. The integration of translanguaging with multimodal elements such as audio and worksheets was found to increase student motivation, participation, understanding, and communication. Students also reported that they felt more confident, found it easier to follow instructions, and were more active in interacting in a bilingual learning environment. Thus, this study concludes that translanguaging integrated with multimodal is an effective pedagogical strategy in English language learning. Based on the limitations of the study, which only focused on audio and visual multimodal, further research is recommended to examine other multimodal.